2013
DOI: 10.3892/ol.2013.1514
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of WWOX, FHIT and p73 in acute lymphoblastic leukemia

Abstract: The aim of the present study was to analyze the expression of WW-domain oxidoreductase (WWOX), fragile histidine triad (FHIT) and p73 in acute lymphoblastic leukemia (ALL). Samples from 122 ALL patients and 35 non-ALL control patients were collected in this study. RT-PCR was performed to detect the mRNA expression of WWOX, FHIT and p73. The methylation status of the WWOX promoter region, FHIT promoter region and the first exon region of p73 were also analyzed using the methylation-specific PCR method. The mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
16
0
3
Order By: Relevance
“…Previous studies have indicated that the methylation status of FHIT may lead to the silencing of gene expression, promoting the occurrence and development of acute lymphoblastic leukemia (17). In the present study, the FHIT gene was found to be expressed in FMSCs, but not in F6 cells.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have indicated that the methylation status of FHIT may lead to the silencing of gene expression, promoting the occurrence and development of acute lymphoblastic leukemia (17). In the present study, the FHIT gene was found to be expressed in FMSCs, but not in F6 cells.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, Chen et al (36) reported that mRNA expression of FHIT was significantly lower and methylation frequency of FHIT was significantly higher in ALL samples compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of the data documented have shown that the expression of WWOX/WWOX was lost or reduced in various types of solid cancers (2)(3)(4)(5)(6)(7)(8)(9)(10). Similarly, the aberration or absence of WWOX/WWOX expression in primary hematopoietic malignancies has also been reported (11)(12)(13)(14)(15)(16). A recently published study detected the expression of WWOX/WWOX in a small cohort of 38 primary leukemia patients and observed low expression levels (14).…”
Section: A B Cmentioning
confidence: 99%
“…A recently published study detected the expression of WWOX/WWOX in a small cohort of 38 primary leukemia patients and observed low expression levels (14). Chen et al (13) recently validated the expression of WWOX in ALL, and observed that the mRNA expression of WWOX, fragile histidine triad and tumor protein p73 was significantly lower in the ALL samples compared with the controls. Correspondingly, the current study showed that WWOX/WWOX expression was reduced or lost in a range of different leukemia types and cell lines in comparison to the normal controls.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation